Limitations of Improved Nitrogen Management to Reduce Nitrate Leaching and Increase Use Efficiency - James L. Baker (The Scientific World Journal)
The primary mode of nitrogen (N) loss from tile-drained row-cropped land is generally nitrate-nitrogen (NO3-N) leaching. Although cropping, tillage, and N management practices can be altered to reduce the amount of leaching, there are limits as to how much can be done. Data are given to illustrate the potential reductions for individual practices such as rate, method, and timing of N applications. However, most effects are multiplicative and not additive; thus it is probably not realistic to hope to get overall reductions greater than 25 to 30% with in-field practices alone. If this level of reduction is insufficient to meet water quality goals, additional off-site landscape modifications may be necessary.